2019
DOI: 10.1371/journal.pone.0225705
|View full text |Cite
|
Sign up to set email alerts
|

Association between circulating neuregulin4 levels and diabetes mellitus: A meta-analysis of observational studies

Abstract: Introduction Neuregulin 4 (Nrg4) was proven as a brown fat-enriched secreted factor that can regulate glucose and lipid metabolism. However, the association between circulating Nrg4 levels and diabetes mellitus (DM) in human remains unclear. We conducted a meta-analysis to investigate association of circulating Nrg4 with DM. Methods Observational studies comparing circulating Nrg4 levels in diabetes patients and health controls were included. Circulating Nrg4, correlation coefficients of clinical indices and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 34 publications
3
11
0
Order By: Relevance
“…In previous studies, NAFLD-related metabolic factors including BMI, HOMA-IR or DM2 were both positively [32][33][34] and negatively [13,[35][36][37] associated with circulating Nrg4 levels in humans. In line with a recent meta-analysis on circulating Nrg4 levels in diabetic patients, we observed no correlation between BMI, HOMA-IR, fasting glucose, blood triglycerides levels and plasma Nrg4 levels [26]. The clinical significance of the observed negative but weak correlation between plasma Nrg4 levels and HDL-C, in line with the finding of Chen et al in diabetic individuals, is doubtful given the unclear role of BAT function on cholesterol levels [38] and even might be the result of multiple testing error [33,34,37].…”
Section: Plos Onesupporting
confidence: 91%
See 2 more Smart Citations
“…In previous studies, NAFLD-related metabolic factors including BMI, HOMA-IR or DM2 were both positively [32][33][34] and negatively [13,[35][36][37] associated with circulating Nrg4 levels in humans. In line with a recent meta-analysis on circulating Nrg4 levels in diabetic patients, we observed no correlation between BMI, HOMA-IR, fasting glucose, blood triglycerides levels and plasma Nrg4 levels [26]. The clinical significance of the observed negative but weak correlation between plasma Nrg4 levels and HDL-C, in line with the finding of Chen et al in diabetic individuals, is doubtful given the unclear role of BAT function on cholesterol levels [38] and even might be the result of multiple testing error [33,34,37].…”
Section: Plos Onesupporting
confidence: 91%
“…1A). Previous reports showed that the presence of type 2 diabetes may influence the level of circulating NRG4 levels [26]. We observed no difference in plasma Nrg4 levels between NAFLD patients with DM2 (n = 16), NAFLD patients without DM2 (n = 49) and HC (n = 43) (P = 0.381) (Fig 1B).…”
Section: Baseline Characteristicsmentioning
confidence: 45%
See 1 more Smart Citation
“… Kang et al (2016) also found increased serum levels of NRG4 in participants with overweight (mean BMI 27 ± 4.02 kg/m 2 ) and type 2 diabetes compared to participants without obesity (mean BMI 24.1 ± 2.65 kg/m 2 ). Consistently, a recent meta-analysis, in which seven studies were included, concluded that circulating NRG4 was associated with alterations in glucose metabolism and obesity ( Wang et al, 2019c ).…”
Section: Introductionmentioning
confidence: 83%
“…where r and r s represent the Pearson’s and Spearman’s CORs, respectively ( 26 ). Cochran’s Q and chi-square tests were used to examine data heterogeneity.…”
Section: Methodsmentioning
confidence: 99%